Hazard Identification and Risk Assessment Using the HIRADC Framework in Travel and Tourist Activities at Mudal River Ecotourism, Kulon Progo, Yogyakarta - Andri Daeng Masiki; Bambang Suhardi; Pringgo Widyo Laksono (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2026)
Introduction: Safety?and security are important considerations for nature-based tourism, even more so if destinations are prone to disasters that reinforce the risk of transport, environmental and activity-related hazards. Kulon Progo, Yogyakarta’s Mudal River Ecotourism reflects these issues through the presence of steep and curving roads, unpredictable hydrometeorological conditions and insufficient safety facilities which together increase risk exposure during travel to?the destination as well as when executing activities at site. Methods: This research used a?qualitative case study approach that purposively juxtaposes the HIRADC framework with the DRR principles in a complex ecotourism context. Data were gathered through fieldwork, semi-structured interviews with managers, tourists and government organizations, document analyses; the risk assessment was based on the AS/NZS 4360:2004 standard considering probability (A–E) and?severity (1–5) scales. Results: The findings identified critical hazards along the travel route (landslides, slippery and narrow roads, brake failure on steep slopes, and interaction with village traffic) and within the tourism area (slipping on rocks, sinking in deep pools, being swept away by strong currents, falls from heights, structurally vulnerable bridges, and animal bites). Most hazards were classified as high risk, particularly those associated with aerial recreation and landslide-prone access, leading to the management of a layered control package that combines engineering measures, administrative procedures, tourist safety education, and community-based monitoring aligned with disaster risk reduction strategies. Conclusion: This study demonstrates how the application of the HIRADC framework and disaster risk reduction concepts can strengthen tourism safety governance in nature-based destinations exposed to geological and hydrometeorological hazards. The proposed safety management roadmap provides a practical reference for destination managers and policymakers and offers insights that can be applied to developing more resilient risk management models in similar ecotourism contexts.